Implementasi Platform Google Classroom sebagai Suplemen Pembelajaran Model Hybrid System pada Mata Pelajaran Pemrograman Dasar di SMK Negeri 4 Malang - Sri Nasatal Ula Chamidah AA; Admaja Dwi Herlambang; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
During the implementation of research basic programming subjects in X Multimedia class at SMK Negeri 4 Malang, the researcher found that basic programming teachers had not brought innovation to the attractiveness of learning materials that used by students. The teacher tried to facilitate students to allow the use of smartphones to access information on learning. Smartphones is able to be used to access various information-learning materials precisely have not been fully utilized. The students prefer to access social media, play online-games rather than looking for learning material. These learning activities show the low-level of initiative and independence of students. With the development of technology in the field of education requires the educators to be more creative and innovative in classroom. An alternative that can be used is a learning model that integrates innovation and technological progress through an online learning-system with interactions between teachers and students. The Hybrid System learning method assisted with interesting material is a solution to overcome student problems related to learning independence. Presenting of interesting material makes students not bored. Hybrid System is a mixture of online-learning and face-to-face meetings in one-integrated learning activity. This learning model can be combined with the implementation of a Learning Management System (LMS) that is Google Classroom. The results after the influence the Hybrid System in Google Classroom, the student obtained a high-category. Because most of the students able to carry out their problems independently. Students who get low-category come before the use of the influence of the Hybrid System.